Knowledge Management and Its Effect on Strategic Decisions of Jordanian Public Universities - Sulieman Ibraheem Shelash Al-Hawary; Abdulazeez Mohammed Alwan (STIE Malangkucecwara, 2016)
This study aims to identify the effect of knowledge management on strategic decisions of the Jordanian public universities in the north region. Knowledge management represented (knowledge identification, knowledge generation, knowledge storing, knowledge dissemination, knowledge applying, knowledge evaluation) as independent variable, either the dependent variable was the strategic decisions and its represented by (decision convenience, decision acceptance and decision quality), tomeasure the variables of the study, the researchers developed a questionnaire and distributed to all managers at various levels of the public universities in the region of north, total (198), and to answer study questions and testing of hypotheses SPSS was used. The researchers found that knowledge management and strategic decision level was mid, as the results showed a statistically significant effect of knowledge evaluation and knowledge storing on strategic decisions at the Jordanian public universities in the north region. Researchers recommend the development of incentives and rewards system for its employees effectively and comprehensively for all management staff and to link these incentives with the actual performance of the staff at the university and continue to use the modern technologies and attract qualified personnel and creative and able to roles of knowledge in universities in north region.